Productivity of apprentices : the impact of school-developed key competencies - Jansen, Anika [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2013)
"In this paper, we analyze the relation between pre-training competencies of apprentices and individual productivity in the training firm. For our analysis, we use firm-level information on the apprentice's oral and written communication skills, basic arithmetic operations skills, basic knowledge of information technology (IT), and problem solving skills and relate this information to the apprentice's productivity level. Controlling for several sources of individual and firm-level heterogeneity, we find that only higher levels of pre-training oral and written skills and problem-solving skills are associated with a higher productivity level of the apprentice." (Autorenreferat, BIBB-Doku)
Keywords: P 2.3 Auszubildende; G 1.2.3.1 Potenziale; Auszubildender; Grundbildung; Schreibkompetenz; Kommunikationsfähigkeit; Mathematische Grundbildung; Informationstechnische Grundbildung; Ertrag; Regressionsanalyse